Generation of long tracts of disease-associated DNA repeats. (February 2005) - Kim, Seung-Hwan; Cai, Lu; Pytlos, Malgorzata J.; Edwards, Sharon F.; Sinden, Richard R.
The generation of long uninterrupted DNA repeats is important for the study of repeat instability associated with several human genetic diseases, including myotonic dystrophy type 1. However, obtaining defined lengths of long repeats in vitro has been problematic. Strand slippage and/or DNA secondary structure formation may prevent efficient ligation. For example, a purified (CTG)140 (CAG)140 repeat fragment containing 4-bp AGCA/TGCT overhanging ends ligated poorly using T4 or Escherichia coli DNA ligase, although limited repeat ligation occurred using thermostable DNA ligase. Here we describe a general procedure for ligating multimers of DNA repeats. Multimers are efficiently ligated when slippage is prevented or when DNA repeats contain a single G/C overhang. A vector is designed from which pure repeat fragments containing a G/C overhang can be generated for further ligation. (CAG)n (CTG)n DNA molecules longer than 800 bp were generated using this approach. This approach also worked for (GAA)n (TTC)n, (CCTG)n (CAGG)n, and (ATTCT)n (AGAAT)n tracts associated with Friedreich ataxia, DM2, and spinocerebellar ataxia type 10, respectively.